2010
DOI: 10.5851/kosfa.2010.30.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Haem Pigments, Peroxide Value, TBARS, Free Fatty Acid Contents and Fatty Acid Composition of Muscles from Low Fat Pork Cuts during Chilled Storage

Abstract: This study was conducted to investigate the changes in haem pigments, peroxide value, TBARS, free fatty acid contents and fatty acid composition of five muscles from low fat pork cuts during storage at 4 o C for 14 d. The myoglobin contents (Oxy, Met and Total) did not change significantly (p>0.05) as storage time increased. In addition, the peroxide value did not change significantly (p>0.05), but the thiobarbituric acid reactive substances were significantly (p<0.05) upregulated during chilled storage. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The analysis for thiobarbituric acid reactive substances (TBARS) was performed with a modified method to measure the degree of lipid oxidation in the sausages . Each sausage was made by adding SN, VN or YN and stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis for thiobarbituric acid reactive substances (TBARS) was performed with a modified method to measure the degree of lipid oxidation in the sausages . Each sausage was made by adding SN, VN or YN and stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance of the supernatant was measured using an ELISA reader at 532 nm. The TBARS value (mg malondialdehyde kg −1 meat) was calculated …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, lipid oxidation of meat can be restrained by low temperature storage, similar to VBN. There have been studies on the effectiveness of refrigeration on lipid oxidation in pork and the results indicated that TBARS values increase with the longer storage periods ( Choi et al, 1998 ; Kim et al, 2004 ; Seong et al, 2010 ). Superchilling was also performed to lower the TBARS of meats.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the degree of the lipid oxidation, TBARS analysis was performed based on a modified method (Buege and Aust ; Jo and others ; Seong and others ). The Jokbal stored at 24 °C was sampled for TBARS analysis on 0, 1, 2, 3, 4, and 5 d while the sampling for the Jokbal stored at 10 °C was conducted using the TBARS analysis on 0, 2, 4, 7, 15, and 30 d. Each of the 5 g of Jokbal treated with 10% rooibos, 4% PL + SDA, or a combination of 10% rooibos and 4% PL + SDA was homogenized with 15 mL DW containing 50 μL of 7.2% dibutylhydroxytoluene in ethanol.…”
Section: Methodsmentioning
confidence: 99%